Penerapan Perangkat Lunak Inovatif Guna Meningkatkan Efisiensi Sistem Manajemen Informasi pada Bank Syariah Indonesia - Zahir Muhammad Fadhilah Harahap; Haya Aghnia Azzahra; Nabila Nasywa; Nurbaiti Nurbaiti (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
This study discusses the implementation of innovative software to improve the efficiency of information management systems at Bank Syariah Indonesia (BSI). The backround of this research begin with growing need for effective and efficient information systems in the digital era, particularly in Islamic banking which requires compliance with sharia principles. The purpose of this study is to identify how software innovation can support better service, data security, and operational effectiveness at BSI. By employing a qualitative descriptive methodology along with a literature review, this research analyzes various technological innovations such as artificial intelligence (AI), big data, and Customer Relationship Management (CRM) applications in Islamic banking systems. The findings show that the adoption of modern information technology significantly enhances operational efficiency, service quality, and competitiveness. The conclusion highlights that software innovation integrated with sharia principles strengthens the management information system and supports BSI’s vision to become a global center of Islamic finance. Future development of software should focus on improving data security and adapting to advanced technologies to further enhance customer service quality.